Pengaruh Fasilitas Terhadap Keputusan Menginap di Homestay Desa Cipasung, Kuningan - Sembiring, Vienna Artina; Taviprawati, Ervina; Darsiah, Anis (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
A rural area that has a unique and distinctive attraction (both in the form of physical attraction / uniqueness of the rural natural environment and social and cultural social life), which is managed and packaged naturally and attractively. Cipasung Village is administratively one of the villages in the Darma subdistrict of Kuningan Regency, having an area of ​​± 151.2 Ha. This village has the potential to develop itself as a tourist village due to natural attractions (such as the Darma Reservoir), village institutions (Bumdes and Kompepar), capacity building (community cohesion), and the potential of tourism facilities (such as housing eligibility for homestays). Homestay is a temporary lodging or resting place that will be used for tourists who vacation in a tourist area. Homestay is also one of the accommodations currently attracting more foreign and domestic tourists. The research method is a deskriptif korelasional, because this study aims to obtain a complete picture of the facilities at the homestay and the decision to stay at the homestay. The results of the study showed that the facility had no effect on the decision to stay at the Cipasung village homestay, Kuningan.